Shifting priorities : understanding physical inactivity from the perspective of female youths - Mohamad Diah, Nurazzura; Samsudin, Suhaiza (2018)
• Globally, many youth are physically inactive. • 4/5 adolescents don’t attain WHO’s recommended guidelines for physical activity with females being more prominent in sedentary lifestyle. • Globally, around 31% of adults aged 15 and above are insufficiently active in 2008 (men 28% and women 34%). • WHO physical inactivity is a key risk factor for noncommunicable diseases (NCDs). •In addition, approximately 3.2 million of deaths each year are attributable to insufficient physical activity.